Real Exchange Rate, Labor Market and Economic Growth in Latin America - Haber, Jeruza; Bornacki de Mattos, Leonardo; Dias de Carvalho, Luciano (Brazilian Keynesian Review, 2023)
The objective of this paper is to empirically analyze the influence of the real exchange rate and the labor market on the economic growth of Latin American countries in the period 2000 to 2014. For that, a “System GMM” model is estimated in which the rate the real exchange rate and the differences in labor productivity, in a dual economy, interact to define different trajectories of growth and functional distribution of income. The results showed that population growth, the average and minimum wage differential - a proxy for the productivity differential - and the participation of wages in income positively influenced the growth of Latin American economies. Furthermore, the devaluation of the real exchange rate has a significant and distinct effect over time on the growth of Latin American economies. Contemporaneously, the influence is negative but, in a lagged way, it is positive (as advocated by the Marshall-Lerner condition). Therefore, it is concluded that the real exchange rate was relevant for the economic growth of Latin America in the period under study.